Epigenetic blockade of neoplastic transformation by bromodomain and extra-terminal (BET) domain protein inhibitor JQ-1 - Zhang, C; Su, Z; Wang, L; Shu, L; Yang, Y; Guo, Y; Pung, D; Bountra, C; Kong, A (Elsevier, 2016)
The neoplastic transformation of cells and inflammation are processes that contribute to tumor initiation. Recently, emerging evidence has suggested that epigenetic alterations are also implicated in the early stages of carcinogenesis. Therefore, potent small molecules targeting epigenetic regulators have been developed as novel cancer therapeutic and preventive strategies. Bromodomain and extraterminal domain (BET) proteins are epigenetic readers that play key roles at the interface between chromatin modification and transcriptional regulation. In this study, we investigated the effect of the BET inhibitor JQ-1 on malignant transformation induced by 12-O-tetradecanoylphorbol-13-acetate (TPA) in mouse skin epidermal JB6 P+ cells. Treatment with JQ-1 effectively impaired TPA-induced colony formation in vitro. At the molecular level, the expression of several key TPA-induced pro-survival and pro-proliferative genes (Bcl2, Cyclin D1, and c-Myc) decreased rapidly after BET inhibition. In addition, JQ-1 treatment attenuated the activation of inflammatory NF-κB signaling triggered by TPA. Luciferase reporter assays using plasmids carrying different elements from the COX2 or IL6 promoters demonstrated that JQ-1 does not directly inhibit interactions between NF-κB and its binding sequence; rather, it affects CRE-element-associated transcriptional enhancement. Through siRNA gene silencing, we found that JQ-1 inhibits the p300-dependent transcriptional activation of COX2, which correlates with the results of the luciferase assay. Chromatin immunoprecipitation assays showed that TPA elevated H3K27Ac enrichment in the COX2 promoter region, which is mediated by p300, and Brd4. JQ-1 treatment did not change H3K27Ac levels but decreased the recruitment of Brd4 and RNA Polymerase II. Collectively, our study reveals that the BET inhibitor JQ-1 exerts potent anti-cancer and anti-inflammatory effects by interfering with the core transcriptional program of neoplastic transformation.